An Ethnobotanical survey of medicinal plants used by traditional healers in the Indian Sundarbans - Mullick, Renia; Sinha, Suchita; Samanta, Dipu; Roy, Debleena (Ethnobotany Research and Applications, 2025)
Background: The Indian Sundarbans, a deltaic ecosystem harbours a diverse array of mangroves and locally available medicinal plants with profound healing benefits. Ethnobotanical practices are inherent to the local communities shaping their healthcare and cultural traditions. As there is limited documentation on the detailed therapeutic potency of these local plants, our work tries to highlight some of them. Methods: Information assembled on the basis of field surveys, by taking random personal interviews of the locals as per a pre-defined list of questionnaire and intensive discussions with the traditional health practitioners like the Gunins, Ojhas, Vaidya’s etc. helped us in documenting some of the ancient traditional knowledge prevalent among these local communities. Results: Our study revealed the therapeutic usage of 31 medicinally significant local plants and 10 prevalent mangrove species in curing a wide range of common as well as chronic ailments. Conclusions: This study thus provides a foundation for future research that integrates traditional knowledge with scientific methods. Collaborative work needs to be encouraged involving the researchers, local communities, and government organizations as it might facilitate investigating the full potential of these plants, furthermore moving towards sustainable development and industrialisation leading to economic benefit of the locals and mankind, thus as a whole resulting in an improved livelihood. Ultimately, relying on these plant-based resources will not only benefit the people residing here but will also stand as a worldwide model, emphasizing the need for conserving our World heritage site. Keywords: Ethnobotany, medicinal property, traditional knowledge, Sundarbans, survey